A Low-Profile Balanced Dielectric Resonator Filtering Power Divider with Isolation - Rong Cai; Chuan Shao; Kai Xu (Micromachines)
A balanced dielectric resonator filtering power divider with isolation performance is proposed. By using the coupling of the <semantics><msubsup>TE111y</msubsup></semantics> modes between three rectangle dielectric resonators, combined with balanced feed structures, the differential-mode filtering and power dividing functions, as well as the common-mode suppression were achieved effectively. Additionally, by technically utilizing the hollow structure of the stacked substrates, isolation resistor structures are introduced at the two output ports to improve the isolation level of the power divider. It can solve the problem of traditional metal-cavity dielectric resonator filter power dividers being unable to add isolation structures due to structural reasons. Compared with the reported dielectric resonator filtering power dividers, the proposed one has the characters of a lower profile and high isolation. For demonstration, one dielectric resonator filtering power divider was fabricated and measured at 11.65 GHz with the profile of 0.66 λg and an isolation higher than 15 dB. The simulation results are in good agreement with the measured results.